Exploring medical teachers' and interns' experiences regarding professional ethics - Zohre Khalajinia; Zahra Alipour; Rohollah Safaeipour (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Medical ethics is a practical subject as well as a branch of ethical philosophy and an integral part of the proper practice in medicine. However, the ethics changes in places and over time and is variable. Furthermore, many issues that have occurred as a result of advances in technology add to the complexity of the ethical issues. Therefore, the objective of this research was to explore medical teachers' and interns' experiences regarding professional ethics. METHODS: This study was a qualitative content analysis conducted on 10 professionals and 10 interns of the surgery and internal departments of medical and educational centers in Qom University of Medical Sciences to discover their experiences of the medical professional ethics. The sampling method was purposive, and data were collected through semi-structured interviews. Data analysis was performed using a qualitative content analysis method with a conventional approach. RESULTS: Three main categories were obtained from the data analysis, including adherence to professional values, organizational conditions, and individual characteristics. CONCLUSIONS: Adherence to professional values, paying attention to individual characteristics, and organizational conditions are among the factors affecting the promotion of medical professional ethics; therefore, it seems that appropriate interventions on these important components can help promote the professional ethics training in the clinical practice.